Laser Cutting of Holes in Inconel 803 Alloy and Analysis of Thermal Stress Field. Issue 1 (2nd January 2019) - Yilbas, Bekir Sami; Akhtar, Syed Sohail; Karatas, Cihan; Ali, Haider; Abu-Dheir, Numan
Abstract: Laser circular cutting of Inconel 803 alloy is carried out. Temperature and stress fields are predicted in the cutting section using ABAQUS finite element code mimicking the experimental conditions. To examine the influence of the hole diameter size on the thermal stress field developed in the cutting section, 2 mm and 10 mm hole diameters are considered in the experiments and analysis. Temperature predictions are validated through the thermocouple data. Morphological and elemental changes in the cutting section are examined incorporating the analytical tools. It is found that laser cut holes are free from large size asperities such as cracks and excessive sideways burnings. However, few small dross attachments are observed at the kerf exit for the small diameter (2 mm) hole. The maximum temperature is higher for small diameter hole than that of the large diameter hole (10 mm) prior to cutting ceases, which is attributed to heat transfer rates from kerf site to its neighborhood. von Mises stress remains low in the region where temperature remains high in the cooling period. This is associated with the elastic modulus of the substrate material, which reduces with increasing temperature. von Mises stress becomes almost same for small and large diameter holes after the cooling period ends and it is in the order of 0.45 GPa.